Mechanisms of lung toxicity induced by biomass burning aerosols - Pardo, Michal (Part Fibre Toxicol, 2020)
BACKGROUND: Carbonaceous aerosols emitted from indoor and outdoor biomass burning are major risk factors contributing to the global burden of disease. Wood tar aerosols, namely, tar ball particles, compose a substantial fraction of carbonaceous emissions, especially from biomass smoldering. However, their health-related impacts and toxicity are still not well known. This study investigated the toxicity of the water-soluble fraction of pyrolyzed wood tar aerosols in exposed mice and lung epithelial cells. RESULTS: Mice exposed to water-soluble wood tar aerosols showed increased inflammatory and oxidative stress responses. Bronchial epithelial cells exposed to the same water-soluble wood tar aerosols showed increased cell death with apoptotic characteristics. Alterations in oxidative status, including changes in reactive oxygen species (ROS) levels and reductions in the expression of antioxidant genes related to the transcription factor Nrf2, were observed and were confirmed by increased levels of MDA, a lipid peroxidation adduct. Damage to mitochondria was observed as an early event responsible for the aforementioned changes. CONCLUSIONS: The toxicity and health effect-related mechanisms of water-soluble wood tar were investigated for the first time in the context of biomass burning. Wood tar particles may account for major responses such as cell death, oxidative stress, supression of protection mechnaisms and mitochondrial damaged cause by expsoure to biomass burning aerosols.